Plan integral de prevención de riesgos laborales para evitar accidentes en los trabajadores de la empresa constructora COMET S.A. de la ciudad de Loja - Cabrera Guerrero, Nayeli Cecibel (2024)
The main purpose of the Integral Plan for the prevention of occupational hazards which focuses on reducing accidents among the employees of COMET S.A., a construction company, consists of development a proposal that guides the company to follow the current regulations and improve the working conditions of its employees. Through the application of descriptive methodology, an analysis and description of the current state of the company are conducted, identifying occupational hazards and determining preventive measures. Three specific techniques are employed: a survey applied to the eight employees, an interview with the manager and direct observation based on a checklist that evaluates compliance with legal regulations on occupational safety and health. Based on the information gathered from the situational diagnosis, the results are as follows: The company provides personal protective equipment to 100% of its employees. The main risks they face include physical hazards such as noise, intense heat, vibrations, etc.; mechanical hazards such as falls from heights, falling objects due to collapse or handling, electrical contact among others; chemical hazards such as excessive inhalation of dust and allergic reactions; and ergonomic risks such as arm pain, leg pain, neck pain, shoulder pain, etc. 25% of the employees have suffered accidents caused by cuts, falls, slips, and being struck by objects; on the other hand, 37.5% have experienced workplace incidents such as slips on stairs, objects falling near employees. As a result, the risk associated with the use of tools and machinery is perceived to be moderate by 75% of employees. In terms of document management, an Occupational Health and Safety Delegate has not been designated. Additionally, the Occupational Health and Safety policy has not been established, as well as there is no training plan. For this reason, it is suggested to the manager to implement the proposed plan in order to minimize costs due to sanctions, reduce the accident rate, and consequently production, and instead safeguard the physical integrity of the employees and promote a culture of self-protection with an environment in good conditions. The budget for the plan will be US$3,647.24.